Comparing proxy and formal measures of county-level racial isolation in race-stratified models: A case study in Tennessee, 2005–2014. (September 2022) - Oka, Masayoshi; Williams, Faustine; Whiteside, Martin
Abstract: The purpose of this study was to understand whether proxy measures of county-level racial isolation (based on racial compositions) would yield similar results as the formal measures of county-level racial isolation (derived from the isolation index of P* ). White (non-Hispanic White) and Black (non-Hispanic Black or African American) women residing in the State of Tennessee, USA, and diagnosed with a non-invasive or invasive breast cancer were considered as the study population. Individual-level variables were obtained from the Tennessee Cancer Registry data for the period between 2005 and 2014 (46, 983 White women and 7, 967 Black women), and county-level variables were obtained from the American Community Survey data for the periods of 2005–2009 and 2010–2014 (95 counties). Using breast cancer condition (non-invasive versus invasive) as the binary outcome of interest, a series of multilevel logistic regression analyses was conducted separately by race. After controlling for individual-level socio-demographic characteristics, proxy measure of county-level White isolation and county-level median household income were not associated with breast cancer condition, but formal measure of county-level White isolation was associated with lower odds of having an invasive breast cancer among White women. On the other hand, neither proxy nor formal measure of county-level Black isolation was associated with breast cancer condition, but county-level median household income was associated with lower odds of having an invasive breast cancer among Black women. These results suggest that using a proxy and formal measure of racial isolation may yield different results, and race-stratified analyses would be helpful for understanding a differential effect of racial isolation on Whites and Blacks. While more detailed examinations are needed in future studies, possible explanations on and reasons behind these findings are discussed. Highlights: County-level White isolation may have a protective effect on White women. County-level Black isolation may have no effect on Black women. County-level racial isolation may have differential effects on races. Measurement may matters for a study of residential segregation and health.